OPTIMIZATION OF GAS TRANSMISSION DESIGN - S LIM, OLIVER MARCT (Universiti Teknologi Petronas, 2011)
Pipelines were first built in the late 1800s to transport low-Btu coal gas through cast iron and lead pipes for street lighting. Long-distance, high-pressure pipelines began operating in the United States in 1891. Pipelines are the most common, and usually the most economic, delivery system tu transport gas from the field tu the consumer. Pipelines are a fixed, long-term investment that can be uneconomic for smaller and more remote gas fields. The volume of gas that can be transported in a pipeline depends on two main factors, which are the pipeline operating pressure and pipe diameter. The maximum diameter of pipelines continues to increase every few years. As diameters of 48 inch become common, the industry may be approaching the practical limit to onshore pipelines. In order to handle the increasing demand, it is likely that operating pressures will increase rather than the size of the pipe. Most transmission pipelines operate at pressures of more than 60 bar, and some operate as high as 125 bar. In order to maintain a high operating pressure, compressors maintain the pressure of gas, and depending on the length of the pipeline and the topography, may be installed at intervals of 150 km to 200 km. Increasing pressure requires larger and thicker pipes, larger compressors, and higher safety standards, all of which substantially increase the capital and operating expenses of a system. The gas industry uses an interesting unit to measure pipeline costs, dollars per inch per kilometer ($/in.-km), measuring the cost of l-in. diameter per kilometer length. This cost has come down, more substantially in offshore pipes where larger diameter and longer distance pipelines are proposed. By some estimates, the cost of offshore lines has reduced from more than $100,000/in.-km to around $25,000 to $40,000/in.-km. Thus, a 400-km, 48-in. line would cost around $480 million to $770 million today, versus double that amount 20 years ago. The rising cost of steel, accounting for 45% of the cost of a typical pjpeline, has offset some of the gains in pipe construction and fabrication costs.